126k views
1 vote
Explain how to write
y -2 =2= -3(x + 6) in standard form using integers

1 Answer

9 votes

9514 1404 393

Answer:

3x +y = -16

Explanation:

Standard form is ...

ax +by = c

where a>0 and a, b, c are mutually prime integers.

__

To get there, we can eliminate parentheses, then separate variable terms from constant terms.

y -2 = -3(x +6) . . . . . given (perhaps)

y -2 = -3x -18 . . . . . . eliminate parentheses

3x +y -2 = -18 . . . . . add 3x

3x +y = -16 . . . . . . . add 2

User Gaurang
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.